Accounting changes in the public sector in Estonia - Tikk, Juta (Business: Theory and Practice, 2010)
This paper reviews the implementation of the accrual accounting in the entities of the Estonian public sector. It gives a brief overview of the historical development of governmental accounting theories and examines the introduction of theory-based accounting policy. It explains main problems and risks to face in connection with the accounting system change process and offers solutions. This study attempts to answer the following research question: how to gain full benefit from accounting information in public sector entities. As to general scientific research methods, mainly comparative analysis and description were used. This study reveals as follows. Firstly, approach to accrual accounting leads to financial information that fulfils needs for true and fair accounting data for decision making purposes. Secondly, reform of public sector financial accounting can improve the quality and the quantity of services provided to the citizens. Thirdly, the Estonian accounting regulation has recently succeeded a remarkable evolution. Fourthly, considerable problems that need to be solved have arisen from the process of the transition to the accrual basis accounting. The given study does not touch upon the development of budgeting systems for public sector entities. Hopefully, this study will contribute to further optimization of accounting systems and management tools for public sector entities in Estonia. Therefore, it will contribute to economic growth and development of business environment. Studies carried out by independent researchers on the move to accrual based accounting in public sector entities are relatively scarce.